Vocabulary interventions for children with developmental language disorder: a systematic review - Ansari, Rafiah; Chiat, Shula; Cartwright, Martin; Herman, Ros (Frontiers in Psychology, 2025)
IntroductionDevelopmental language disorder (DLD) is a neurodevelopmental condition often characterised by vocabulary difficulties that lead to academic and social challenges. The acquisition of vocabulary is a complex, dynamic process of mapping word sound (phonology) to meaning (semantics) supported by contextual cues; a complexity that vocabulary interventions need to address. To understand the key features and impact of such interventions, a systematic review of word-learning studies involving children aged 5–11 with DLD was conducted.MethodA structured search covered seven electronic databases for the period 1990–2023. In addition, the reference lists of identified studies were searched manually. Studies were appraised for quality and data was extracted relating to word-learning effectiveness and intervention characteristics. Findings were reported as written summaries and quantitative data ranges.ResultsSixteen relevant studies were identified with most appraised as medium quality. Interventions tended to be delivered individually in school by speech and language therapists. The most common outcome measure was expressive target-word tests, such as picture naming and word definitions. Interventions explicitly targeting phonological and semantic word features had the most high-quality studies reporting significant vocabulary gain. The inclusion of stories to provide context implicitly during phonological and semantic interventions was beneficial, though stories alone were less effective. Specificity in learning was noted across studies. Gains did not generally transfer to non-targeted words and showed depreciation following therapy. Intervention responses were influenced by children's language profiles. For example, children with more severe language difficulties were less responsive to contextual cues during story reading and were more distracted by extraneous music during multimedia-supported word learning.DiscussionWhilst the available studies have limitations in range and quality, they do suggest some benefits of combining explicit and implicit vocabulary strategies and considering children's presenting profiles. Implications for practitioners supporting the individual needs of children with DLD are discussed. This includes addressing issues with the generalization and maintenance of vocabulary gains by targeting the most relevant words and encouraging recall and self-management strategies. Further research should explore the influence of home-school carryover.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022327345, PROSPERO, Reg: CRD42022327345.